Effect of Rearing Temperature on Offspring Fitness in Drosophila bipectinata - Santhosh, Hassan T; Krishna, Mysore S (Asian Journal of Biological and Life Sciences, 2015)
The thermal environment experienced by an individual during development has a direct and indirect effect on the female preference for their mate. A great diversity of male traits such as size, colour, pigmentation, courtship song, mating call are known to be used by female in mating decision to obtain direct and indirect fitness benefits. Male age is one such male trait that has received a lot of attention as a possible cue for female mating decision. In D. bipectinata, offspring of females mated with young, middle aged and old-aged males reared at three different temperatures were analyzed to test the good-gene model associated with female preference for male age on the one hand and whether or not a father produces successful offspring on the other. Adult fitness traits are important components of fitness traits that a father can give to his offspring. Our results in the present study suggest that sons of old-aged males had greater reproductive success than sons of young and middle-aged males.
Keywords: D. bipectinata; Female preference; Offspring fitness; Rearing temperature